Perbandingan Kinerja Reksadana Pendapatan Tetap Syariah dan Reksadana Saham Syariah yang Terdaftar di OJK Periode 2017-2021 - Eka Nurmala Sari; Syarief, M. Edman (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
This study aims to determine the differences in the performance of sharia mutual funds which are of the type of sharia fixed income and sharia stock mutual funds for the 2017-2021 period. The sample data was determined by random sampling method and resulted in twelve Islamic mutual funds consisting of six Islamic fixed income mutual funds and six Islamic equity mutual funds. The analytical methods used include the classic assumption test, the Independent Sample T-test, the Mann Whitney test with the performance measurement of sharia mutual funds using the Sharpe, Treynor, Jensen and AUM Growth. The results of this study indicate that the performance of Islamic fixed income mutual funds is higher than the performance of Islamic stocks using the Sharpe method, and in the Treynor, Jensen and AUM Growth methods the performance of Islamic equity mutual funds is higher than the performance of Islamic fixed income mutual funds.